2022
DOI: 10.1063/5.0093655
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic manipulation dynamics of levitated particle with screw-shaped reflecting surface

Abstract: Existing single-axis acoustic levitation devices with an axisymmetric reflector can manipulate particles in a variety of ways. However, the mechanism by which particles are suspended in a single-axis acoustic levitator with a non-axisymmetric reflector remains poorly understood. This work addresses this issue by proposing a novel single-axis ultrasonic levitator design that includes a flat plane emitter and a screw-plane reflector. The node positions of the standing wave formed in this levitator were predicted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Additionally, unlike traditional Langevin horns, where adjusting the focus requires complex structures [25] and the inability to actively control the focus position when adjusting the inclination angle [16,17,26], array-type acoustic levitation devices offer greater flexibility. Phase modulation allows array-type devices to actively change the focus in the optimal operating region when the structure varies, especially when the array rotates (φ = ϕ for concave array and φ = ϕ/2 for planar array).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, unlike traditional Langevin horns, where adjusting the focus requires complex structures [25] and the inability to actively control the focus position when adjusting the inclination angle [16,17,26], array-type acoustic levitation devices offer greater flexibility. Phase modulation allows array-type devices to actively change the focus in the optimal operating region when the structure varies, especially when the array rotates (φ = ϕ for concave array and φ = ϕ/2 for planar array).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Space simulation research has turned out to be particularly important due to the high cost and limited opportunity of on-orbit space experiments.Acoustic levitation is an effective containerless processing method for simulating space environment. [9][10][11][12] The phenomenon of acoustic levitation was first observed by Kundt [13] in 1866. He found that sound waves in a resonance tube could levitate dust particles.…”
mentioning
confidence: 99%
“…Acoustic levitation is an effective containerless processing method for simulating space environment. [9][10][11][12] The phenomenon of acoustic levitation was first observed by Kundt [13] in 1866. He found that sound waves in a resonance tube could levitate dust particles.…”
mentioning
confidence: 99%